2015
DOI: 10.1371/journal.pone.0115895
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Prognostic Biomarker of Advanced Urothelial Carcinoma

Abstract: ObjectivesSarcopenia, a novel concept reflecting the degenerative loss of skeletal muscle mass, is an objective indicator of cancer cachexia. We investigated its role as a prognostic biomarker in advanced urothelial carcinoma (UC) patients.MethodsThis retrospective study consisted of 88 UC patients with cT4 and/or metastases to lymph nodes/distant organs. Skeletal muscle index (SMI), an indicator of whole-body muscle mass, was measured from computed tomography (CT) images at the diagnosis. Sarcopenia was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 30 publications
3
87
0
3
Order By: Relevance
“…An association between sarcopenia and survival has also been described for other solid malignancies including gastrointestinal, biliary tract, lung, urothelial, colorectal, pancreatic, and metastatic breast cancer. 6,8,12,14,34,35 Other studies showed a correlation of sarcopenia and therapyinduced adverse effects. 8,30,36 We used the cutpoint of 38.5 cm 2 /m 2 for sarcopenia that was proposed by Prado et al 6 As a matter of fact, this cutpoint resulted in the best stratification in terms of predicting survival also in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An association between sarcopenia and survival has also been described for other solid malignancies including gastrointestinal, biliary tract, lung, urothelial, colorectal, pancreatic, and metastatic breast cancer. 6,8,12,14,34,35 Other studies showed a correlation of sarcopenia and therapyinduced adverse effects. 8,30,36 We used the cutpoint of 38.5 cm 2 /m 2 for sarcopenia that was proposed by Prado et al 6 As a matter of fact, this cutpoint resulted in the best stratification in terms of predicting survival also in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate muscle mass, and possibly greater muscle mass than noncancer patients, has been shown to be a strong determinant of overall mortality in several studies of cancer patients. (28-39) Studies of CRC patients with advanced disease found that muscle wasting was associated with worse recurrence-free and/or overall survival(40) as well as poor response to chemotherapy. (41) Persons with low muscle mass experience elevated low-grade systemic inflammation,(42) and altered mitochondrial function,(43, 44) both of which may influence cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia, either on its own or as a central component of cachexia, is defined as muscle depletion “two standard deviations below the mean of a young reference group” [5]. In studies with cancer of the gastrointestinal-tract (GI), breast cancer and lung cancer, sarcopenia was associated with poor survival [4, 610]. Moreover, sarcopenia is associated with higher rates of chemotherapy-induced toxicity [11, 12].…”
Section: Introductionmentioning
confidence: 99%